On the partial sums of Vilenkin-Fourier series - George Tephnadze (Հայաստանի ԳԱԱ)
The main aim of this paper is to investigate weighted maximal operators of partial sums of Vilenkin-Fourier series. Also, the obtained results we use to prove approximation and strong convergence theorems on the marting Hardy spaces Hp, when 0 < p ≤ 1.
Keywords: Analysis; Mathematics; Science